2021
DOI: 10.1051/e3sconf/202131901044
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the microbiological and hygienic quality of turkey meat between six districts of the Kenitra city

Abstract: Meat is known to be one of the vehicles for many diseases to humans. The aim of this study is the comparison of the microbiological and hygienic quality of fresh turkey meat marketed in the most popular districts of Kenitra city. Fresh meat samples were taken from stores localized in six different districts. Microorganisms tests were conducted according to the appropriate standards. The Aerobic Mesophilic Flora (AFM) was most counted in district five (7.69±0.212 log10ufc/g), while the highest total and fecal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
0
5
1
Order By: Relevance
“…The obtained results in Staphylococcus aureus counts are consistent with Martínez-Laorden, et al [33], who found 2.52 log CFU/g. however, Jaber, et al [34] found a higher Staphylococcus aureus counts than our study. The results of this investigation showed that the mould and yeast were lower than those of Vural, et al [35], who reported an 88.18% rate.…”
Section: Discussioncontrasting
confidence: 74%
“…The obtained results in Staphylococcus aureus counts are consistent with Martínez-Laorden, et al [33], who found 2.52 log CFU/g. however, Jaber, et al [34] found a higher Staphylococcus aureus counts than our study. The results of this investigation showed that the mould and yeast were lower than those of Vural, et al [35], who reported an 88.18% rate.…”
Section: Discussioncontrasting
confidence: 74%
“…The enumeration of staphylococci is carried out on a selective Chapman medium. Cultures are incubated at 37 °C for 24 to 48 hours [44].…”
Section: Pathogenic and Toxigenic Flora -Staphylococcus Enumerationmentioning
confidence: 99%
“…The antibacterial activity was evaluated against 78 strains of Escherichia coli isolated from turkey meat marketed at the point of sale, as previously studied [19].…”
Section: Examined Microorganismmentioning
confidence: 99%
“…The essential oil of each plant was tested to determine its antibacterial power using the disc diffusion method [18]. Petri dishes containing Mueller-Hinton agar medium were flooded with 1 ml of preculture of pathogenic bacteria.…”
Section: Aromatogrammentioning
confidence: 99%
See 1 more Smart Citation